STUDI IMPLEMENTASI KEBIJAKAN STANDAR PELAYANAN MINIMAL PENDIDIKAN (Studi Pada SDN Di Wilayah Kelurahan Lamekongga Kecamatan Wundulako Kabupaten Kolaka) - Jurnal Governance Jurnal Kebijakan & Manajemen Publik; MUH. ZAENAL AM. (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2010)
Autonomy and decentralization policy of education of course very suitable with democratic principles, but which we have to concern is whether local government can provide educational services with the adequate quality. It is important to note because of the inproportionale ability condition between each local governments. Referring to this matter, The Minister of National Education have made decision number 053 year 2001 concerning guidance compilation of Minimum service standard for Elementary educational and Middle school management. Execution of this standard in the regional sub-district Lamekongga have been well done. There are at least four factors affecting namely communications, resource, disposition, and structure of bureaucracy.